The Counterparts in the Ancient Iraqi Literature and Pre-Islamic Poetry A STUDY IN SUBJECTS AND IDEAS (Journal of the College of Languages (JCL), 2025)
This research paper aims studying the topics and ideas which ancient Iraqi literature in its poetic and prosaic and other arts in comparison with its counterpart in the ancient poetry of the Arab during in the Pre-Islamic era. I have observed importance of study of these counterparts while reading many of the literary texts of the two literatures. A valuable reference by the late professor Dr. Abdul-Jabbar Al-Mutalabi in which he affirmed that the ancient Arab poem remained habiting other worlds that are not free of the remnant of long-established fears and rituals. This research is an attempt to reveal the similar themes in the two literatures whether in the views, ideas of artistic like the wild pull and the wild cow, stories if immortality, travel of knowledge seeking in addition to themes that formed a common feature between the ancient Iraqi literature and pre-Islamic poetry. The link between these two literatures is rampant with examples. The research is divided into two aspects: the first cares for the important intellectual and life themes and other purpose, the second is concerned with the descriptions of the counterpart in the literatures.